Snap-shot of the ultrasound school of the Spanish Society of Rheumatology - E. Naredo; J. Uson (PAGEPress Publications, 2011)
Today, there is no doubt that musculoskeletal ultrasonography (MSUS) is the rheumatologists' best tool. It extends physical examination, aids clinical approach and is a very attractive research tool. Ultrasound schools for rheumatologists' are developing fast in many countries. Let's have a look at the Ultrasound School of the Spanish Society of Rheumatology (USSSR). Back in 1996, Esperanza Naredo, Lucia Mayordomo and myself started the USSSR. We had the privilege to be trained by Dr. Antonio Bouffard and Dr. Marnix Van Holsbeeck, eminent radiologists and fathers of MSUS from Henry Ford Hospital in Detroit, Michigan....